(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2021)
Backdrop: Aortic atherosclerosis continues to be a complex process, with the genetic factors, personal lifestyles, alterations in local hemodynamics, vascular injury, age related changes, endothelial inflammation and autoimmune diseases, all contributing to its pathogenesis. The scenario of atherosclerosis in India is appalling with highest loss in potentially productive years of life. As study of atherosclerosis in living population is difficult, invasive and expensive especially in the developing countries, autopsy studies have been proved to be a good method for assessing atherosclerosis. So, the present study was planned to evaluate the prevalence of atherosclerosis, with the clinic-demographic profiles of the victims of aortic atherosclerosis and analysing the risk factors associated with it. Material and Methods: This is a cross-sectional descriptive study which was conducted to detect aortic atherosclerosis among all the deceased who got referred to R.G. Kar Medical College Police Mortuary for autopsy between 1st April to 30th September, 2014. Resusts: Majority of the victims belonged to 4th to 8th decades, with male preponderance in all the age groups. Though the residence has got no significant implication on atherosclerosis, age turned out to be the single most culprit in the pathogenesis of atherosclerosis, with hypertwnsion, hyperlipidemia, hyperglycemia and smoking playing their significant parts. Conclusion: The authors feel, in most cases, atherosclerosis can be prevented as most risk factors associated with this illness are directly connected with the lifestyle of an individual. In this regard, educational campaign that focuses on informing the members of the society about the dangers of atherosclerosis, its causes, and the ways of its prevention is likely to reduce the occurrence of this disease and thus improve the overall health level of the nation.